The general perspective of Information Management profession / Ain Farzanah Mohd Husaini - Mohd Husaini, Ain Farzanah (Faculty of Information Management, 2014)
In Malaysia, the Information Management field seems a bit vague and not very recognizable as the citizen of Malaysia has a little the knowledge regarding it. This matter actually affected the profession and carrier of the people who study and work in this field and there are severe effects of it in the information society of the country. Information management can be describe as the ability to manage a process of production, control, maintain, storage and retrieval of all the information plus ensuring the right information immediately available to the right people, in the right place, at the right time using the lowest budget like it has been stated by Langemo, 1980. People's perspectives toward this field play a big role as this will help the knowledge development in information management becoming an impact to the country information system and being applied in all the other field of knowledge to have a good management system.